Association between internet usage and healthcare expenditure among middle-aged and older Chinese adults with chronic diseases: the role of self-rated health - Yiqing Xing; Clifford Silver Tarimo; Ruibo He; Haomiao Li; Weicun Ren; Liang Zhang (BMC Public Health)
Abstract Background Middle-aged and older people are high-risk groups for chronic disease morbidity, and the healthcare expenditure burden they face has become an important social issue that must be addressed. Although the internet serves as a key tool for health management, little is known about its role in the healthcare expenditure of these groups. This study aims to explore how internet usage is associated with healthcare expenditure among middle-aged and older adults with chronic conditions, along with the underlying mechanism. Methods The study employed data from the Chinese Family Panel Survey (CFPS) conducted between 2014 and 2018. The sample was restricted to individuals aged 45 years or above with chronic diseases (n = 12,601). The fixed effects model was used to investigate the relationship between internet usage and healthcare expenditure of respondents. Instrumental variable method, subsample regression, supplementary variable method and propensity score matching were adopted to test robustness. The Karlson–Holm–Breen method and an IV-based mediation method were also used to assess the mediating effect of self-rated health. Results Findings indicate that internet usage is significantly associated with lower healthcare expenditure burden among respondents (β = -0.068, P < 0.001). Self-rated health plays a mediating role in the relationship between internet usage and healthcare expenditure, accounting for 30.14% of the effect. Heterogeneity analysis reveals that internet usage is significantly associated with lower other expenditures (β = -0.112, P < 0.001) while being associated with higher hospital expenditure (β = 0.094, P < 0.05). Analysis of urban–rural heterogeneity further reveals that internet usage is significantly associated with higher hospital expenditure in rural areas (β = 0.145, P < 0.05). However, the association between internet usage and other expenditures in urban areas (β = -0.217, P < 0.001) is greater than that in rural areas (β = -0.035, P < 0.01). Conclusions These findings highlight internet usage is associated with a lower expenditure burden of middle-aged and older adults with chronic diseases in China, mediated by high self-rated health. In addition, urban–rural disparities in the association between internet usage and healthcare expenditure are significant.